Suicidal No Longer - Hoover, M. A.; Paulson, B. L. (Canadian Journal of Counselling and Psychotherapy, 2007)
In this phenomenological study, participants who had been suicidal were interviewed and asked, "What was helpful in suicidal healing?" Participants' stories of healing were analysed thematically. The metaphor of "A Journey Away From the Self" describes the participants' suicidal processes as disconnection from others and from the self: their feelings, their self-worth, and their ability to negotiate their lives. The "Return to the Self" describes their healing as reconnection with others and with the self, developing new perspectives of the self and living, becoming self-accepting, self-advancing, and self-enduring. This investigation of the suicidal person's perspective contributes the voice of those "Suicidal No Longer." The thematic structure identifies processes that have implications for conceptualizing and directing treatment.